2012
DOI: 10.1097/acm.0b013e318253676a
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Performance of U.S. Teaching and Nonteaching Hospitals

Abstract: Teaching hospitals offer advanced clinical capabilities, educate the next generation of providers, care for disadvantaged urban populations, and are leaders in health care research and innovation. However, many stakeholders may be unaware of an additional value-relatively higher quality and safety in many areas, with similar adjusted costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 38 publications
3
111
2
Order By: Relevance
“…One explanation for this finding is that academic hospitals care for highly complex patients who might be particularly vulnerable to discontinuities in care. 31 A second explanation is the confounding that might be introduced if patients with severe or unusual illnesses were directed to subspecialty academic centres for readmission. A third explanation focuses on differences in organizational culture between academic and community hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for this finding is that academic hospitals care for highly complex patients who might be particularly vulnerable to discontinuities in care. 31 A second explanation is the confounding that might be introduced if patients with severe or unusual illnesses were directed to subspecialty academic centres for readmission. A third explanation focuses on differences in organizational culture between academic and community hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of earlier reports, we also examined annual case volume (integer) and sector (designated as academic sector or community sector by system-level hospital reports) of the readmission hospital. [29][30][31][32][33] Variables were modelled as continuous values unless otherwise indicated but are presented in categories to facilitate interpretation.…”
Section: Variablesmentioning
confidence: 99%
“…Shahian and colleagues found that intense hospital teaching status was associated with lower patient satisfaction, which brings to question the role of patient perceptions and overall satisfaction relative to a patient's likelihood to recommend a provider. [16] This discrepancy might be explained by the varying patient perceptions of care or the need to study more about what influences patients' likelihood to recommend a hospital or provider to others since this is just one measured component of patient satisfaction. It is also noteworthy that the higher the percentage of patients over the age of 65, the lower the likelihood that a patient would recommend a hospital others.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16] We perform a retrospective analysis based on data availability and because this is an observational study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation